Neuronal differentiation dictates estrogen-dependent survival and ERK1/2 kinetic by means of caveolin-1. - Floriana Volpicelli; Massimiliano Caiazzo; Bruno Moncharmont; Umberto di Porzio; Luca Colucci-D'Amato (PLoS ONE, 2014)
Estrogens promote a plethora of effects in the CNS that profoundly affect both its development and mature functions and are able to influence proliferation, differentiation, survival and neurotransmission. The biological effects of estrogens are cell-context specific and also depend on differentiation and/or proliferation status in a given cell type. Furthermore, estrogens activate ERK1/2 in a variety of cellular types. Here, we investigated whether ERK1/2 activation might be influenced by estrogens stimulation according to the differentiation status and the molecular mechanisms underling this phenomenon. ERK1/2 exert an opposing role on survival and death, as well as on proliferation and differentiation depending on different kinetics of phosphorylation. Hence we report that mesencephalic primary cultures and the immortalized cell line mes-c-myc A1 express estrogen receptor α and activate ERK1/2 upon E2 stimulation. Interestingly, following the arrest of proliferation and the onset of differentiation, we observe a change in the kinetic of ERKs phosphorylation induced by estrogens stimulation. Moreover, caveolin-1, a main constituent of caveolae, endogenously expressed and co-localized with ER-α on plasma membrane, is consistently up-regulated following differentiation and cell growth arrest. In addition, we demonstrate that siRNA-induced caveolin-1 down-regulation or disruption by means of ß-cyclodextrin treatment changes ERK1/2 phosphorylation in response to estrogens stimulation. Finally, caveolin-1 down-regulation abolishes estrogens-dependent survival of neurons. Thus, caveolin-1 appears to be an important player in mediating, at least, some of the non-genomic action of estrogens in neurons, in particular ERK1/2 kinetics of activation and survival.